Vps35‐dependent recycling of Trem2 regulates microglial function. (1st November 2016) - Yin, Jie; Liu, Xiaocui; He, Qing; Zhou, Lujun; Yuan, Zengqiang; Zhao, Siqi
Abstract : Triggering receptor expressed on myeloid cells 2 (Trem2), an immune‐modulatory receptor, is preferentially expressed in microglia of central nervous system. Trem2 might be involved in the development of Alzheimer's disease (AD) through regulating the inflammatory responses and phagocytosis of microglia. However, the intracellular trafficking of Trem2 remains unclear. In this study, we showed that Trem2 in the plasma membrane underwent endocytosis and recycling. Trem2 is internalized in a clathrin‐dependent manner and then recycled back to the plasma membrane through vacuolar protein sorting 35 (Vps35), the key component of cargo recognition core of retromer complex, but not Rab11. When Vps35 is knocked down, Trem2 accumulated in the lysosomes but was not degraded. More importantly, Vps35 deficiency leads to excessive lipopolysaccharide (LPS)‐induced inducible nitric oxide synthase (iNOS) expression and IL‐6 production, which can be abolished by Trem2 overexpression. Furthermore, R47H Trem2, an AD‐associated mutant, failed to interact with Vps35 and became unstable compared with wild‐type Trem2. Our study suggests that Vps35/retromer is responsible for recycling of Trem2 in the regulation of microglial function such as proinflammatory responses, whereas R47H mutation impairs Trem2 trafficking, which might contribute to AD. Abstract : Model for vacuolar protein sorting 35 (Vps35)‐mediated triggering receptor expressed on myeloid cells 2 (Trem2) recycling. Wild‐type Trem2 is internalized in a clathrin‐dependent manner then trafficked to cell membrane through Vps35. By recycling Trem2, Vps35 is involved in suppressing proinflammatory responses of microglia. However, the R47H mutant Trem2 is impaired in interacting with Vps35 and accumulated in lysosome for degradation.